Student Perception of Social Loafing in University Teamwork - Singer, Carey (Organisational Psychology, 2020)
This study investigated perceptions of social loafing in undergraduate student teams at a South African university. Student participants, randomly assigned to teams, received coursework instruction about team dynamics (including social loafing) and worked together for 12 weeks on a team assignment that was graded at the end of the semester. Students (n = 243) wrote individual reflections on the reasons for social loafing in student teams. Some (n = 24) also participated in an experiential social loafing exercise. These two sources of qualitative data were used in the development of a survey questionnaire, which was completed by 229 students. Fifty-four percent of the student participants (n = 229) perceived social loafing to have occurred in their teams. Four components of perceived social loafing behaviour were identified using factor analysis: unavailability, poor work quality, tech loafing and discussion non-contribution. Loafer apathy (a general lack of care or interest) predicted significant variance in each of the four loafing behaviours and social compensation. Team performance (assignment grades) was not related to the perceived presence social loafing in a team. Rather than reducing effort in response to perceived social loafing (the sucker effect), a social compensation effect occurred in the perceived presence of poor work quality. Effective leadership moderated the relationship between loafer apathy and tech loafing as well as loafer apathy and social compensation. Practical implications and recommendations for future research are presented.